The determinants of electric and hybrid vehicle adoption: a perspective from Serbia - Mitić, Petar; Kojić, Milena; Hanić, Aida; Fedajev, Aleksandra; Radulescu, Magdalena; Dembińska, Izabela (Serbian Journal of Management, 2025)
This study investigates the factors influencing the intention to purchase electric and hybrid vehicles in Serbia. It draws upon socio-demographic characteristics, social influence, environmental concerns, and policy measures to gain a nuanced understanding of the complexities of adopting sustainable transportation alternatives in Serbia. Using descriptive and inferential statistics, decision tree analysis, and logistic regression enabled a rigorous examination of the determinants influencing attitudes and intentions toward electric and hybrid vehicles (EHVs). The findings emphasized the importance of positive evaluation from influential individuals and the introduction of higher taxes on more polluting vehicles as important factors that impact electric and hybrid vehicle adoption according to all three applied methods. In addition to these factors, the results from the two applied methods further highlight the significance of household income, the positive societal perception of EHVs, and the belief that EHVs contribute to reduced pollution. Since age, residence, education level, and household size do not emerge as significant factors influencing respondents’ intention to purchase EHVs and all remaining factors appear to be relevant according to only one of the applied methods, the focus should be placed on the factors identified as significant by either two or all three methods. Such results provide a solid basis for policy recommendations in Serbia to promote electric and hybrid vehicles adoption.